Implementasi Nilai-Nilai Pendidikan Karakter Religius Dalam Kitab Minhajul Abidin Karya Imam Ghazali Di Pondok Pesantren Al Falah Putri Banjarbaru Kalimantan Selatan - Nahdiyah; Halilah (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This study discusses the implementation of religious character education values ​​in the Minhajul Abidin book by Imam Ghazali at the Al Falah Putri Islamic Boarding School, Banjarbaru, South Kalimantan. The formulation of the problem in this study is how is the implementation of religious education values ​​and what factors are the supporters and obstacles in the application of Minhajul Thalibin at the Al-Falah Putri Islamic Boarding School. This type of research is conducted in the form of field research. The subject in the subject of this study is a teacher of morals in the Ulya class of the Al-Falah Putri Islamic Boarding School, Banjarbaru, South Kalimantan. The object of this study is the implementation of religious character education values ​​in the Minhajul Abidin Book by Imam Gazali at the Al-Falah Puteri Islamic Boarding School, Banjarbaru, South Kalimantan. Data collection techniques in this study are observation, interviews and documentation. For data analysis using qualitative descriptive analysis by describing the actual events in the form of sentence descriptions, then the final conclusion is drawn. From the results of the study, the following conclusions can be drawn: First, the implementation of the Value of Patience in the Minhajul Abidin Book. There are four applications of the value of patience, patience in carrying out worship and obedience, patience from committing sins, patience from doing useless and excessive things in the world, patience in facing trials and disasters. Second, the implementation of the Value of Gratitude in the Book of Minhajul Abidin. Implementing a sense of gratitude for the blessings that have been received so far, namely the blessing of health, the blessing of being able to breathe, the blessing of being able to walk, and many more blessings that need to be grateful for. Third, the implementation of the Value of Sincerity in the Book of Minhajul Abidin. Implementing sincerity is accepting with a sincere heart that whatever Allah's provisions are, whether it is happy, sick or sad, everything must have its own wisdom. Supporting and inhibiting factors include: Supporting Factors consist of 1. Internal Supporting Factors: a. Awareness or life conditions that are realized by oneself., b. Being grateful to be able to go to school, c. Motivating yourself to study harder. 2. External Supporting Factors: a. Family environment, b. Parents, c. Teachers, Ustadz and Ustadzah, d. Friends. Inhibiting factors consist of 1. Internal Inhibiting Factors: a. Weak personality of students, b. Lack of motivation, c. Lack of confidence in one's own abilities. 2. External Inhibiting Factors: a. Students often forget their purpose of studying at the Islamic boarding school, b. Learning is not supported by oneself c. Staying at the boarding school only because there are still friends. Keywords: Religious Character, Minhajul Abidin, Al-Falah Putri Islamic Boarding School Abstrak Penelitian ini membahas tentang implementasi nilai-nilai pendidikan karakter religius dalam kitab Minhajul Abidin karya Imam Ghazali di Pondok Pesantren Al Falah putri Banjarbaru Kalimantan Selatan Rumusan masalah dalam penelitian ini adalah bagaimanakah implementasi nilai pendidikan religius dan faktor apa saja yang menadi pendukung dan penghambat dalam pengaplikasian Minhajul Thalibin di Pondok Pesanteren Al-Falah Putri. Jenis penelitian ini dilakukan dalam bentuk penelitian lapangan.Subjek dalam Subjek penelitian ini adalah seorang guru mata pelajaran akhlak di kelas Ulya pondok pesantren Al-Falah Putri Banjarbaru Kalimantan Selatan. . Objek penelitian ini adalah implementasi nilai-nilai pendidikan karakter religius dalam Kitab Minhajul Abidin karya Imam Gazali di Pondok Pesantren Al-Falah Puteri Banjarbaru Kalimantan Selatan.Teknik pengumpulan data dalam penelitian ini yaitu, observasi, wawancara dan dokumentasi. Untuk analisis data menggunakan analisis deskriptif kualitatif dengan mendiskripsikan kejadian yang sesungguhnya dalam bentuk uraian kalimat, kemudian diambil kesimpulan akhir. Dari hasil penelitian dapat diambil kesimpulan sebagai berikut: Pertama, implementasi Nilai Sabar dalam Kitab Minhajul Abidin. Penerapan nilai sabar ada empat, sabar dalam melaksanakan ibadah dan ketaatan, sabar dari berbuat maksiat, sabar dari melakukan hal-hal yang tidak berguna dan berlebihan didunia, sabar dalam menghadapi ujian dan musibah. Kedua, implementasi Nilai Syukur dalam Kitab Minhajul Abidin. Menerapkan rasa bersyukur akan nikmat yang telah diterima selama ini, yaitu nikmat sehat, nikmat bisa bernafas, nikmat bisa berjalan, dan masih banyak lagi nikmat-nikmat yang perlu disyukuri. Ketiga, implementasi Nilai Ikhlas dalam Kitab Minhajul Abidin. Menerapkan ikhlas itu menerima dengan hati yang ikhlas bahwa ketentuan Allah apapun itu, mau itu senang, sakit ataupun menyedihkan, semuanya pasti mempunyai hikmah tersendiri. Faktor pendukung dan penghambat antara lain:Faktor Pendukung terdiri dari 1. Faktor Pendukung Internal: a. Kesadaran atau kondisi kehidupan yang disadari oleh diri sendiri., b. Bersyukur bisa bersekolah, c. Memotivasi diri sendiri untuk lebih giat belajar. 2. Faktor Pendukung External: a. Lingkungan keluarga, b. Orang tua, c. Para Gutu Ustadz dan Ustadzah, d. Teman. Faktor penghambat terdiri dari 1. Faktor Penghambat Internal: a. Kepribadian santri yang lemah, b. Kurangannya motivasi, c. Tidak percaya diri pada kemampuan diri sendiri.2. Faktor Penghambat External: a. Seringanya santri lupa akan tujuannya belajar di pondok pesantren, b. Belajar bukan dukungan dari diri sendiri c Bertahan dipondok hanya karna masih ada teman. Kata kunci: Karakter Religius, Minhajul Abidin, Pondok Pesantren Al-Falah Putri